The generality of changes in the trait composition of fish and invertebrate communities after flow restoration in a large river (French Rhône). (30th March 2015) - Dolédec, Sylvain; Castella, Emmanuel; Forcellini, Maxence; Olivier, Jean‐Michel; Paillex, Amael; Sagnes, Pierre
Summary A multiple‐trait‐based approach can provide predictions and interpretations of the responses of freshwater communities to river restoration that apply in different taxonomic contexts. We compared the observed and predicted effects of restoration on sets of traits in fish and invertebrate communities in four reaches of the Rhône River. Restoration included minimum flow increases in three bypassed main channels and the reconnection of eight floodplain channels. Predictions (described in detail in three other articles in this Special Issue) were based on habitat models that related the density of modelled taxa to their physical habitats. We used trait information extracted from the literature to translate predicted taxonomic changes into predicted changes in traits. Observed changes in traits calculated for modelled taxa and for all taxa in the community were both compared to predictions. In 10 of 12 cases, observed changes in traits correlated with predicted ones. With few exceptions, the agreement was higher for fish and invertebrates in the main channels than for invertebrates in floodplain channels. Predictions translated to the trait category level improved those at the taxonomic level in 5/6 and 4/6 cases for modelled taxa and all taxa, respectively. However, the improvement was statistically significant according to a null model for 1/6 and 3/6 cases for modelled taxa and all taxa, respectively. The validation of trait predictions suggested that traits related to locomotion and attachment, as well as general biology and physiology, were particularly suited to predicting and understanding the effects of physical restoration. For example, after restoration, clingers and passive filter feeders dominated invertebrate communities in the main channels, whereas invertebrate communities in the floodplain underwent a selection of traits frequent in running water (clingers, flattened shape and gill respiration). Within fish communities, the periodic life‐history strategy that characterises fish species in downstream reaches (long life span, large body, late sexual maturity) increased with restoration, whereas the opportunistic strategy decreased. Our results suggest that a better understanding of how hydraulics shapes traits in riverine systems is critically needed for assessing the effects of restoration measures impacting flow. In addition, existing trait databases (especially for fish) should be expanded to better reflect the energetic trade‐offs that organisms must make in various flow contexts.